RETRACTED: The Role of Communication in Thought - Johnson, DMan (Disability Studies Quarterly, 2011)
Retraction Notice: The Editors-in-Chief retract the article entitled "The Role of Communication in Thought" published in Disability Studies Quarterly, 2011, 31 (4), http://dx.doi.org/10.18061/dsq.v31i4.1717. Our decision to retract is due to major overlap with a previously published work: Johnson, DMan (2011). "The Role of Communication in Thought." The Communicator 20(1): 4-5. http://www.autcom.org/pdf/AutcomNLWinter2011.pdf The original article was published on October 25, 2011, and was retracted on April 18, 2017. The retracted article will remain online to maintain the scholarly record, and will be marked as retracted. Keywords facilitated communication, literacy, Pinker, Piaget Abstract If people believe that people who do not talk do not think, they will believe that they have nothing to contribute. People look at facilitated communication users and think that they learned to think only after getting the means to communicate. They are working under the assumption that the only way to learn language is through interaction. I use ideas from Harvard neurologist Steven Pinker, studies of gifted children, and other evidence to demonstrate that people likely use language from the earliest moments of infancy, even before they can talk.